Globalizing Europe : deepening integration, alliance capitalism, and structural statecraft - Brewer, Thomas L.; Brenton, Paul.; Boyd, Gavin (Cheltenham, Glos., UK ; Northampton, MA : Edward Elgar Pub., 2002)
This text examines the involvement of the European Union in the deepening integration that results as trade and transnational production link markets and economic systems across the world. This process is posing a unique challenge to European decision-makers to implement measures.
Includes bibliographical references and index.
opc 30/09/16
Loans
Keywords: Economic integration; Economic policy; Globalization; European Union countries